Paradoks Salib: Keindahan Wajah Kemuliaan Allah - Umbara, Joko (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2019)
An experience of the cross of Jesus Christ in Christian theology brings the sense of paradox. Christ’s death on the cross reflects the fate of humanity within the context of Christian faith. The cross is also seen as a mystery that tells the tragic story of humans who accept their punishment. However, the cross of Jesus Christ also reveals meanings that challenge Christians to find answers in their contemplation of the cross. The cross becomes a stage for human tragic drama, which might also reveal the beauty of death and life. It is the phatos of humanity, for every human being will die, but it is also seen as the tree of life hoped for by every faithful. On the cross is visible God’s self-giving through the love shown by the crucified Christ. God speaks God’s love not only through words, that is, in the teachings of Jesus Christ, but also through Christ’s loving gesture on the cross. The cross of Christ is the culmination of God’s glory and through it, God’s glory is shown in the beauty of divine love.